The end of men : and the rise of women - Rosin, Hanna (New York : Riverhead Books, 2012)
Men have been the dominant sex since the dawn of mankind. But Hanna Rosin has noticed that this long-held truth is, astonishingly, no longer true. At this unprecedented moment, by almost every measure, women are no longer gaining on men: they have pulled decisively ahead. And "the end of men"--the title of Rosin's Atlantic cover story on the subject--has entered the lexicon as dramatically as Betty Friedan's "feminine mystique," Simone de Beauvoir's "second sex," Susan Faludi's "backlash," and Naomi Wolf's "beauty myth" once did. In this landmark book, Rosin reveals how this new state of affairs is radically shifting the power dynamics between men and women at every level of society, with profound implications for marriage, sex, children, work, and more. With wide-ranging curiosity and insight unhampered by assumptions or ideology, Rosin shows how the radically different ways men and women today earn, learn, spend, couple up--even kill--has turned the big picture upside down.--From publisher description
Introduction -- Hearts of steel : single girls master the hook-up -- The seesaw marriage : true love (just for elites) -- The new American matriarchy : the middle class gets a sex change -- Pharm girls : how women remade the economy -- Degrees of difference : the education gap -- A more perfect poison : the new wave of female violence -- The top : nice-ish girls get the corner office -- The gold misses : Asian women take over the world -- Conclusion
Includes bibliographical references and index
Keywords: Women -- Social conditions -- 21st century; Women -- Economic conditions -- 21st century; Feminism